Obtenção de filmes absorvedores solares a base de cromo: caracterização óptica e morfológica - Medeiros, Ithyara Dheylle Machado de (2020)
The development of new solar energy technologies is considered to be one of the many key solutions to meet a growing global demand for energy. However, growth in the field of solar energy faces several technical barriers. Thus, the development of new materials and technologies to increase the efficiency of solar thermal collectors is a challenge and a necessity. In view of the above, the present study sought to manufacture solar absorber films based on chromium using two manufacturing techniques (electrodeposition and sputtering). The electrodeposition occurred through the variation of four parameters (chemical composition, voltage between the terminals, anode-cathode working distance and time spent in the bath). The electrodeposited coatings were covered by an antireflective layer (AR) based on residual sugarcane ash. Films without and with the AR layer were characterized optically and morphologically. Through the sputtering technique, the work sought to develop a new type of absorbent film consisting of multi-layers of chromium and silicon, which had their absorption levels evaluated. The results showed that the coatings manufactured by both techniques showed absorption averages at the commercial level (above 90%). In addition, the AR coverage increased the efficiency of the films, especially those deposited on copper substrates (highlighting an increase from 84 to 92%). Through statistical analysis it was determined that the composition of the bath and the tension between the terminals were the two most significant parameters for obtaining films with high levels of absorption through the electrodeposition technique (with a 97% reliability rate). Films produced in multilayers by the sputtering technique showed higher levels of absorption than those deposited only with the chromium layer.